Toward Better of English Language Teaching (ELT) in Islamic Senior High Schools Padang - Luli Sari Yustina; Besral Besral; Hasnawati Hasnawati (Peneliti.net, 2022)
This research aims to explore the teaching and learning process of English as a Foreign Language (EFL) in Islamic Senior High Schools in Padang. The main objective of the study is mainly to assess the teachers’ competence in developing students' speaking skills based on their ability to plan, conduct, and evaluate the learning process. The objects of this study revealed several English teachers in three different Islamic Senior High Schools of Padang. Data were collected from English teachers’ Lesson Plans and video recordings of their teachings. Based on the analysis, it was found that most teachers failed to show appropriate performances as required by the curriculum. The study finally concludes that ELT in this specific area has been abused, and therefore, serious attention must be paid to better improvement in the future. Detail of each competence are elaborated and discussed in the paper and conclusion as well as recommendation are also presented